51 The Importance of Planning: A comparison of the use of Advance Care Plans in the care home and hospital setting. (14th March 2023) - Fleming, Elizabeth; Spriggs, Helena; Pelham, Anne; Tarala, Elizabeth; Brown, Jolene
Abstract : Background: Average life expectancy in UK care homes is 24 months in residential care and 12 months in nursing care. The Department of Health defines 'End of Life' as the last 12 months of a person's life and encourages advance care planning (ACP) discussions. In the North East Emergency Health Care Plans (EHCP) and Care for the Dying Patient Document (CDP) are used to support ACP and end of life care. This review compared to what extent ACPs were present for people who died in a hospital setting as opposed to a care home setting. Methods: Two retrospective audits reviewed notes of care home residents who died between April and October 2021. Audit one (A1) reviewed the notes of patients who died within seven days of admission to hospital using hospital records and recorded whether an ACP was present(n=69). Audit two (A2) reviewed notes of residents who died in a care home for evidence of ACP (n=67). Results: A1 showed 54 residents had a Do Not Attempt Cardiopulmonary Resuscitation form (DNACPR) in place prior to admission and 16 had an EHCP. A2 demonstrated 59 residents had a DNACPR and 40 had an EHCP. 38 of the EHCPs in A2 advised that hospital admission should be avoided. No care home residents in A1 were supported by the CDP document prior to admission. 30 residents from A1 died within 48 hours of admission into hospital. In A2 34 had an admission to hospital in the last three months of life. 37 residents in A2 were supported by the CDP. Conclusions: Residents who died in care homes had more evidence of ACP than those who died in hospital. This may suggest that ACP has a role in prevention of hospital admission for care home residents.